2014
DOI: 10.1155/2014/696904
|View full text |Cite
|
Sign up to set email alerts
|

Reusable Component Model Development Approach for Parallel and Distributed Simulation

Abstract: Model reuse is a key issue to be resolved in parallel and distributed simulation at present. However, component models built by different domain experts usually have diversiform interfaces, couple tightly, and bind with simulation platforms closely. As a result, they are difficult to be reused across different simulation platforms and applications. To address the problem, this paper first proposed a reusable component model framework. Based on this framework, then our reusable model development approach is ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The proposed system discussed in this paper is a continuation of our prior work [22]. The prime purpose of this work is to introduce a framework where code reusability can be tested and analyzed with varied ranges of near real-time problems associated with software development.…”
Section: The Proposed Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed system discussed in this paper is a continuation of our prior work [22]. The prime purpose of this work is to introduce a framework where code reusability can be tested and analyzed with varied ranges of near real-time problems associated with software development.…”
Section: The Proposed Solutionmentioning
confidence: 99%
“…There are mainly four essential stages involved in designing proposed framework e.g. i) in the first stage, we take sample object-oriented source code from two software projects and extracts its software metric values with respect to Coupling between objects, Response for classes, weighted methods per class, Depth of inheritance tree, Number of Children, ii) in the second stage, we introduce 4 different problems in software development as case study, iii) in the third stage, we compute code reusability using concept mentioned in [22], and iv) we apply optimization technique to ensure reliability of the outcome obtained for code reusability. This part of the study formulates an empirical approach for further computing the coding attribute, Where, the variable P represents product of software metrics, total effort, and hours of work.…”
Section: The Proposed Solutionmentioning
confidence: 99%
“…Yao and Zhu et al [3] proposed a reusable model development specification -RUM, as shown in figure 1, which defines the interface of model initialization, input data and output data etc. RUM can improve PDES application development efficiency and provide basis for automatic testing.…”
Section: Rummentioning
confidence: 99%
“…Reusable simulation model development Specification RUM [3] can reduce the difficulty of model integration and improve the development efficiency of PDES application. In addition, RUM provides a basis for automatic code generation of simulation models.…”
Section: Introductionmentioning
confidence: 99%
“…Because the simulation model services released and stored in the cloud center have differences in attributes, functions, and quality of service (QoS), it is necessary to find and select the appropriate simulation model that accurately meets the user's requirements in terms of function and can provide high QoS for building complex system simulation applications [5]. Reusable model development (RUM) specification [6] cannot support network communication between a simulation model and a simulation engine under the cloud architecture. Ontology web language [7] (OWL)-based simulation model search methods lack the mechanism to search simulation models through the correlations between models.…”
Section: Introductionmentioning
confidence: 99%